Solar Automation Locking System - Balang, Timothy Pengiran; Shabani, Hikma (Progress in Engineering Application and Technology, 2022)
Door locking mechanism is the most crucial component to keep houses and offices safe from robberies. Nowadays, door locking mechanism has been revolutionize to the modern door locking system with. This system can be found in several types to unlock and lock the mechanism by using RFID, fingerprint and password. Approaching with the latest technology which is Internet of Things (IoT), the proposed door locking system is able to monitor and control the activity of the door trough smartphones. Based on the research has been conducted, solar automation locking system able to deliver the criteria needed to solve the problem by notifying and monitor by user through Blynk application in their smartphone with the presence of magnetic sensor. Magnetic sensors are used in this system to monitor the door activity whether it is close or open and notify user through Bynk application. Hence, in this system where Node MCU is connected to Wi-Fi which powered by solar technology and interacting in the application to control the locking mechanism.